Chemokine receptors: multifaceted therapeutic targets - Proudfoot, Amanda E. I. (Nat Rev Immunol, 2002)
Chemokines and their receptors are involved in the pathogenesis of diseases ranging from asthma to AIDS. Chemokine receptors are G-protein-coupled serpentine receptors that present attractive tractable targets for the pharmaceutical industry. It is only ten years since the first chemokine receptor was discovered, and the rapidly expanding number of antagonists holds promise for new medicines to combat diseases that are currently incurable. Here, I focus on the rationale for developing antagonists of chemokine receptors for inflammatory disorders and AIDS, and the accumulating evidence that favours this strategy despite the apparent redundancy in the chemokine system.